1990
DOI: 10.1351/pac199062091773
|View full text |Cite
|
Sign up to set email alerts
|

Properties of coatings and applications of low pressure plasma spray

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10]. The mixture ratio of kerosene to oxygen was fixed at the stoichiometric ratio for complete combustion.…”
Section: Warm Spray Conditionsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10]. The mixture ratio of kerosene to oxygen was fixed at the stoichiometric ratio for complete combustion.…”
Section: Warm Spray Conditionsmentioning
confidence: 99%
“…Sanz reported that high velocity oxygen fuel (HVOF) sprayed WC‐17%Co coatings showed superior wear resistance and lower abrasion rates as compared to a new generation weld overlay coating. Other thermal spray coating materials used on process rolls involve Cr3C2‐NiCr and ZrO2‐MgO‐(WC‐12Co) for guide rolls, WC‐Ni‐Cr for continuous galvanizing lines, and WC‐Co for bridle rolls. Under high operating temperatures, as in the case of stainless steel production, thermal barrier coating (TBC) systems are widely used for oxidation and high temperature resistance.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Also, commercial (Cr and WC based) coating powders with oxide content are mostly preferred for protective coating of caster roll surfaces with APS method. 1,4,5,[16][17][18][19][20][21] In this study, an alternative protective coating material (ferrochromium slag) is introduced for deposition as a top coat layer on the surface of the caster rolls using APS technique, in accordance with TBC principle. Ferrochromium (FeCr) is a metal compound used in stainless and thermalresistant steel production.…”
Section: Introductionmentioning
confidence: 99%
“…However, service life of welded coatings is limited due to formation of thermal cracks and vapor oxidation and these coatings exhibit low toughness as mentioned above . Also, commercial (Cr and WC based) coating powders with oxide content are mostly preferred for protective coating of caster roll surfaces with APS method …”
Section: Introductionmentioning
confidence: 99%